Uji Kepekaan Bakteri Klebsiella sp. Hasil Isolasi Ulkus Diabetes Pasien Rawat Inap Di RSUD Dr. Moewardi terhadap Antibiotik Meropenem, Gentamisin, Seftriakson, dan Siprofloksasin pada Bulan Februari-Maret Tahun 2014 - Ima Fatimah; Kisrini Kisrini; D. Andang Arif Wibowo (Jurnal Farmasi Indonesia, 2015)
Diabetic ulcer is an open wound on the surface of the skin caused by macroangiopati so insufisiensi and vascular neuropathy, diabetic ulcer, if not immediately get treatment and care, it will be easy to make the infection extends and immediately in case of any further action requiredamputation. The purpose of this study was to isolate Klebsiella sp. isolation of sufferers of diabetes ulcer purulence inpatients in RSUD Dr. Moewardi and knowing the pattern of sensitivity antibiotics gentamicin, seftriakson, meropenem, ciprofloxacin and against bacteria Klebsiella sp. in February-March 2014. Purulence samples obtained was isolated on media Mac Conkey, continued staining grams and biochemistry test. Antibiotic sensitivity test refers to the standard Kirby Bauer, to analyze the data using Oneway ANOVA. The study is done against 30 samples purulence patients ulcer diabetes in RSUD Dr. Moewardi February-March 2014, 18 positive samples containing Klebsiella sp. and 12 negative samples Klebsiella sp. antibiotic meropenem 100% sensitive, sensitive 100% ciprofloxacin, gentamicin resistant 96,29% and 3,71% intermediate, seftriakson 94,50% resistant and 5,50% moderately suspectible.